Electrochemical Sensor Based on Glassy Carbon Electrode Modified with Carbon Nanohorns (Swcnh) for Determination of Cr(Vi) Via Adsorptive Cathodic Stripping Voltammetry (Adcsv) in Tap Water - Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Pizarro-Reyes, J; Pizarro-Reyes, J; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; Liendo-Ibarra, F; Liendo-Ibarra, F; Penagos-Llanos, J; Penagos-Llanos, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this study, a new and simple glassy carbon electrode modified with carbon nanohorns (SWCNH/GCE) was used for the determination of Cr(VI) in aqueous matrices via adsorptive cathodic stripping voltammetry (AdCSV). The modified electrode was characterized via field emission scanning electron microscopy and cyclic voltammetry, which revealed a homogeneous distribution of spherical agglomerates of SWCNH on the electrode surface. The modification increased the electrochemically active area from 0.10 cm2 ± 0.01 (GCE) to 0.16 cm2 ± 0.01 (SWCNH/GCE). The optimized analytical conditions were as follows: a supporting electrolyte (0.15 mol L−1 HCl), an accumulation potential of 0.8 V versus Ag/AgCl, and an accumulation time of 240 s. Validation of the analytical methodology was performed, obtaining a linear range between 20 and 100 µg L−1, a limit of detection of 3.5 µg L−1, and a limit of quantification of 11.6 µg L−1 with good accuracy and precision. The method was applied to the analysis of spiked tap water samples, and the results were compared using a flame atomic absorption spectrophotometer (FAAS) with no significant statistical differences. © 2024 by the authors.
Keywords: carbon nanohorns; modified electrode; chromium (VI); AdCSV